Hamlet - Shakespeare, William, 1564-1616; Durband, Alan (Woodbury, N.Y. : Barron's, 1986)
Presents the original text of Shakespeare's play side by side with a modern version, discusses the author and the theater of his time, and provides quizzes and other study activities.
Keywords: Shakespeare, William, -- 1564-1616 -- Outlines, syllabi, etc; Hamlet -- (Legendary character) -- Drama; Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Kings and rulers -- Succession -- Drama; Murder victims' families -- Drama; Fathers -- Death -- Drama; Revenge -- Drama; Princes -- Drama; Plays; English literature -- History and criticism; Denmark -- Drama